Consumer Behaviour for Life Insurance Industry: An Indian Perspective: Understanding the Impact of Demographics on Consumer Buying Behavior in the Indian Life Insurance Industry (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Consumer behaviour is the study of when, why, how, and where people do or do not buy a products/services. It blends elements from psychology, sociology, social anthropology and economics. The study of consumer behavior provides marketers to understand and predict the future market behavior. Life Insurance is the fastest growing sector in India since 2000 as Government allowed Private players and foreign direct investment (FDI) up to 26%. Life Insurance in India was nationalized by incorporating Life Insurance Corporation of India (LIC) in 1956. Life insurance industry in India being in nascent stage has been found very sensitive to myriads of issue particularly when we talk of buying pattern. Consumer choice of one product over other products has been the issue of concern for many of the researcher and for the organization, who has already putted lot of hard work in developing the product. This paper discuss about the effect of demographical element in consumer buying behavior in Life Insurance Industry in India.